REFORMULASI PERBUATAN CONTEMPT OF COURT DI DALAM SISTEM PERADILAN PIDANA INDONESIA - NIM. A1011171073, DANIEL ALFREDO TAMBUNAN (Jurnal Fatwa Hukum, 2022)
AbstractThis research is a study of the reformulation of contempt of court acts in the Indonesian criminal justice system, where the object under study is contempt of court acts regulated in positive law and future law, positive law, namely the Criminal Code (KUHP) and various other laws and regulations, while the future law is the Draft Criminal Code (RKUHP) chapter VI regarding criminal acts against the process Judicial. Contempt of court is defined as acts, behaviors, attitudes and/or speech that can demean and undermine the authority, dignity, and honor of the judiciary. The author focuses on research on the scope and limits of acts regulated in the Indonesian criminal justice system and also some actions that are considered necessary to be regulated in future laws.The writing method used is a normative research method with an analytical descriptive approach, the type of data used is secondary data, and data analysis is carried out by qualitative juridical methods. The author conducts an assessment using the theory of the division of contempt of court acts, including the behavior of despicable and inappropriate behavior in court (misbehaving on court), not obeying court orders, attacking integrity and impartiality of the court (scandalizing the court), obstructing justice, contempt of court is done by way of publication (sub judice rule).The results of the research that has been carried out have found that the regulations regarding the conduct of contempt of court in positive law are scattered in various regulations and are regulated randomly, but the regulated acts have been quite diverse in regulating from each stage in the criminal justice system, while in the RKUHP there has been clarity about the actions that are regulated because they are specifically regulated in a chapter. The deeds regulated in both have many similarities, in other words, there are actions that are regulated in the positive law adopted into the law being drafted. In addition to the similarities, there are also differences in the two, there are actions that are regulated in the designed law while not regulated in positive law, there are also actions that are regulated in positive law but not regulated in the designed law. The author also provides several views on the classifications studied either in the form of actions that the author considers necessary to be added or actions that are considered necessary to be further refined.Based on the results of the author's analysis, the author draws several conclusions, namely that the contempt of court acts regulates every act in all stages of the criminal justice system, the acts in this criminal act can also be done by anyone, be it the public or law enforcement. Keyword: Contempt of Court; Criminal Code Bill; Criminal Justice System Abstrak Penelitian ini merupakan kajian mengenai reformulasi perbuatan contempt of court dalam sistem peradilan pidana Indonesia, dimana objek yang dikaji adalah perbuatan-perbuatan contempt of court yang diatur dalam hukum positif dan hukum yang akan datang, hukum positif yaitu Kitab Undang-Undang Hukum Pidana (KUHP) dan berbagai peraturan perundang-undangan lainnya, sementara hukum yang akan datang adalah Rancangan Kitab Undang-undang Hukum Pidana (RKUHP) bab VI mengenai tindak pidana terhadap proses peradilan. Contempt of court diartikan sebagai perbuatan, tingkah laku, sikap dan/atau ucapan yang dapat merendahkan dan merongrong kewibawaan, martabat, dan kehormatan badan peradilan. Penulis menitik beratkan penelitian pada cakupan dan batasan perbuatan-perbuatan yang diatur dalam sistem peradilan pidana Indonesia dan juga beberapa perbuatan yang dianggap perlu diatur dalam hukum yang akan datang.Metode penulisan yang digunakan adalah metode penelitian normatif dengan pendekatan deskriptif analitis, jenis data yang digunakan adalah data sekunder, dan analisis data dilakukan dengan metode yuridis kualitatif. Penulis melakukan pengkajian menggunaka teori pembagian perbuatan contempt of court, antara lain berprilaku tercela dan tidak pantas di pengadilan (misbehaving on court), tidak menaati perintah-perintah pengadilan (disobeying court orders), menyerang intergritas dan impartialitas pengadilan (scandalizing the court), menghalang-halangi penyelenggaraan pengadilan (obstructing justice), penghinaan terhadap pengadilan dilakukan dengan cara publikasi (sub judice rule).Hasil penelitian yang telah dilakukan didapati bahwa peraturan mengenai perbuatan contempt of court dalam hukum positif tersebar didalam berbagai peraturan dan diatur secara acak, akan tetapi perbuatan yang diatur sudah cukup beragam mengatur dari setiap tahap dalam sistem peradilan pidana, sementara itu dalam RKUHP telah terdapat kejelasan mengenai perbuatan yang diatur karena diatur secara khusus dalam suatu bab. Perbuatan-perbuatan yang diatur dalam keduanya memiliki banyak persamaan, dengan kata lain terdapat perbuatan-perbuatan yang diatur didalam hukum positif yang diadopsi kedalam hukum yang sedang dirancangkan. Selain terapat persamaan juga terapat perbedaan didalam keduanya, terdapat perbuatan yang diatur didalam hukum yang dirancangkan sedangkan tidak diatur dalam hukum positif, terdapat juga perbuatan yang diatur dalam hukum positif tetapi tidak diatur dalam hukum yang dirancangkan. Penulis juga memberikan beberapa pandangan terhadap klasifikasi-klasifikasi yang dikaji baik berupa perbuatan-perbuatan yang penulis anggap perlu ditambahkan ataupun perbuatan-perbuatan yang dianggap perlu untuk lebih disempurnakan.Berdasarkan hasil analisis penulis maka penulis menarik beberapa kesimpulan yaitu perbuatan contempt of court mengatur setiap perbuatan dalam semua tahap sistem peradilan pidana, perbuatan dalam tindak pidana ini juga bisa dilakukan oleh siapa saja baik itu masyarakat maupun penegak hukum. Kata Kunci: Contempt of Court; RUU KUHP; Sistem Peradilan Pidana